Identificación de peptidos inmunogenicos de Toxoplasma gondii: Selección por ensayos ex vivo en muestras humanas HLA-A*02 (2015)
It is known that CD8+ T cells are the subpopulation that plays an important role in the protective immunity against Toxoplasma gondii. The use of synthetic peptides from constitutive proteins or with an immunogenic potential as vaccine candidates are used to elicit a cytotoxic response. The immune response to peptides from proteins P30 and ROP18 of Toxoplasma in human lymphocytes with or without toxoplasmosis was analyzed. Population and proliferation of lymphocytes was determined by flow cytometry and levels of cytokines IL10 and IFN-γ in culture supernatant of lymphocytes was measured by ELISA. It was found that peptides from P30 and ROP18 are immunogenic and induce proliferation mainly on CD4+ over CD8+ and elicit production of IL10 over IFN-γ. Peripheral blood mononuclear cells (PBMCs) from HLA-A*02 individuals seropositive and seronegative for Toxoplasma were isolated to test if new peptides predicted by bioinformatics with high affinity for HLA-A*02 are recognized in the context of an infection by Toxoplasma. The immune response is lower when induced with P30 and ROP18 peptides than with GRA3 peptides. A new search for epitopes using bioinformatics tools allowed identifying a new set of peptides from which 4 (Got1, Ter1p, LMBR, PLA2) showed a good stimulation of IFN-γ in human HLA-A*02 PBMCs from Toxoplasma seropositive but not from seronegative individuals measured by ELISpot. A new rational methodology based on bioinformatics tools for Toxoplasma vaccine candidates is presented.